Diversity in Surface Microstructures of Trichomes, Epidermal Cells, and Stomata in Lentil Germplasm - Patel, Ishita; Gorim, Linda Yuya; Tanino, Karen; Vandenberg, Albert (Frontiers in Plant Science, 2021)
To develop crops capable of withstanding challenges posed by climate change, breeding strategies must focus on addressing multiple stresses occurring concurrently in plants. Leaf epidermal structures such as trichomes, stomata, and epidermal cells play an important role in mediating plant defense and could be essential traits that impart wide-ranging tolerance to biotic and abiotic stresses. Consequently, it is important to inform on the underlying diversity in these traits in lentil germplasm (Lens spp.). In this study, we characterized foliar microstructures of 12 genotypes belonging to seven wild and cultivated Lens species. We performed scanning electron microscopy on leaflet and pod surfaces for their qualitative characterization. For quantitative characterization, we observed surface imprints via light microscopy and quantified trichome density (TD), trichome length (TL), stomatal density (SD), epidermal cell density (ECD), and stomatal index (SI) on adaxial and abaxial leaflet surfaces for each genotype. We also assessed heritability of trichome traits by evaluating interspecific recombinant inbred lines (RILs) derived from the cross L. culinaris CDC Redberry x L. tomentosus IG 72805. Comparing foliar microstructures, we found that TD and TL varied widely among cultivated and wild lentil genotypes. However, in most lentil genotypes, the adaxial leaflet surface had lower TD and longer trichomes compared to the abaxial surface. Pubescence on pods comprised five major phenotypes: no trichomes or glabrous pods, very short trichomes at low density, short trichomes at high density, medium length trichomes at high density, and long trichomes at high density. Leaves of all species were amphistomatous and SI, SD, and ECD were all higher on the adaxial compared to the abaxial surface. Adaxial surfaces had slightly sunken stomata, which might be an adaptive trait to conserve water. Quantifying TD and TL on leaflets of interspecific RILs revealed transgressive segregation of these traits, suggesting that TD and TL are quantitative in nature. While taxonomic implications of this study are limited, detailed description of agronomically relevant morpho-physiological traits presented in this paper along with the mode of inheritance of trichomes may serve as a resource for scientists developing lentil adapted to concurrent biotic and abiotic stresses of the future.